2008
DOI: 10.1590/s1414-81452008000400008
|View full text |Cite
|
Sign up to set email alerts
|

Freqüência de lesões perineais ocorridas nos partos vaginais em uma instituição hospitalar

Abstract: Durante o parto normal, a maioria das mulheres sofre algum tipo de lesão perineal, em razão de lacerações espontâneas ou como conseqüência da incisão cirúrgica - episiotomia. Este estudo, do tipo descritivo, com abordagem quantitativa, visa levantar a freqüência de lesões perineais ocorridas em mulheres durante o parto vaginal em uma instituição hospitalar que exerce a obstetrícia tradicional. A amostra foi composta por 279 prontuários de mulheres que pariram na instituição durante o período de julho a dezembr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
1
4
0
6
Order By: Relevance
“…According to the authors, this fact complicates the understanding of birth physiology, limits the knowledge about their bodies, about the changes caused by pregnancy and about their rights, being at the mercy of the decision of professionals. 14 Regarding the obstetric history, the present study found a higher incidence of first pregnancy. Similarly, a study performed on a referral center in the state of Pernambuco in order to analyze the prevalence and factors associated with episiotomy in 495 women undergoing vaginal delivery showed that primiparous and women with no previous vaginal delivery presented ten times greater risk of being subjected to the procedure than pregnant women in general.…”
Section: Discussionsupporting
confidence: 45%
“…According to the authors, this fact complicates the understanding of birth physiology, limits the knowledge about their bodies, about the changes caused by pregnancy and about their rights, being at the mercy of the decision of professionals. 14 Regarding the obstetric history, the present study found a higher incidence of first pregnancy. Similarly, a study performed on a referral center in the state of Pernambuco in order to analyze the prevalence and factors associated with episiotomy in 495 women undergoing vaginal delivery showed that primiparous and women with no previous vaginal delivery presented ten times greater risk of being subjected to the procedure than pregnant women in general.…”
Section: Discussionsupporting
confidence: 45%
“…Confirming our study, Mouta et al 20 have found 73.4% of perineal traumas, of which 68.52% were lacerations. On the other hand, Santos et al 2 have shown that from 279 analyzed medical charts, there has been episiotomy without laceration in 86.99% of women. Risks of the routine use of episiotomy are well known, stressing that its restricted use has clear advantages, such lower incidence of posterior perineal trauma or more severe perineal traumas, lower incidence of pain and postpartum complications, in addition to the lack of evidence of better maternal or perinatal results with episiotomy 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Non-probabilistic sample was intentional and by convenience, and data were processed and analyzed by the Statistical Package for the Social Sciences (SPSS) version 16 (SPSS Inc., Chicago, IL, United States of America, Release 16.0. 2,2008). Exploratory analysis of variables was carried out after coding variables in a database and validation by double entry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudo realizado com o objetivo de analisar a ocorrência de lesão perineal severa em parto vaginal, mostrou uma prevalência de episiotomia em 45,7% das pacientes, mas a literatura mostra que pode chegar a 90,24%. 10 Devido às sequelas no corpo feminino causada pelas lacerações perineais graves, se torna importante a avaliação de fatores assistenciais associados ao parto, com objetivo de combater os fatores evitáveis. No intuito de avaliar esses fatores, realizamos um estudo na Maternidade Escola Assis Chateaubriand (MEAC), que é um serviço de referência em atenção terciária em obstetrícia no estado do Ceará, onde ocorre um grande número de partos (em torno de 130 partos vaginais no mês).…”
Section: Introductionunclassified